Effects of smokeless tobacco on cell viability, reactive oxygen species, apoptosis, and inflammatory cytokines in human umbilical vein endothelial cells. (13th June 2021) - Zhao, Junwei; Qiao, Liangjun; Shang, Pingping; Hua, Chenfeng; Xie, Yuming; Li, Xiang; Ding, Meizhou; Liu, Kejian; Guo, Junwei; Zhao, Ge; Wang, Sheng; Liu, Huimin; et al.
Abstract: Smokeless tobacco products provide an alternative to cigarettes; however, smokeless tobacco is carcinogenic and harmful to human health. This study evaluated the toxicological effects of snus extracts and cigarette smoke total particulate matter (TPM) on human umbilical vein endothelial cells (HUVECs). Treated cells were examined for cell viability, reactive oxygen species (ROS), apoptosis, and inflammatory cytokines. Moreover, we explored the mechanism of programmed cell death induced by snus. The results showed that snus extracts significantly inhibited cell viability in a dose-dependent manner. ROS was significantly increased in treatment groups, and anti-oxidant treatment could not prevent snus extract-induced cell death. Snus extracts induced apoptosis, DNA damage, activation and cleavage of caspase-3 and caspase-8, pathway-related gene change, and interleukin (IL)-6 and IL-8 release in HUVECs. Snus extracts exposure may induce cytotoxicity, ROS generation, inflammatory cytokines release, and apoptosis or DNA damage through intrinsic and extrinsic pathways in HUVECs.